2002
DOI: 10.1029/2001jd000595
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Arctic polar stratospheric clouds in the winter of 1996/1997 inferred from ILAS measurements

Abstract: [1] The Improved Limb Atmospheric Spectrometer (ILAS) captured many polar stratospheric cloud (PSC) events in the Northern Hemisphere during the winter and early spring of 1997. Simultaneous measurements of nitric acid and aerosols by ILAS made it possible to infer PSC composition. The aerosol extinction coefficient and nitric acid data were compared with the theoretically predicted values for supercooled ternary solution (STS), nitric acid dihydrate (NAD), and nitric acid trihydrate (NAT) at thermodynamic equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 56 publications
(94 reference statements)
0
35
0
Order By: Relevance
“…Thus, care should be taken especially when ILAS observed ice PSCs. In this study we eliminated all the ozone data that may have been affected by PSCs occurrence, according to the information on PSCs detection provided by Saitoh et al [2002].…”
Section: Datamentioning
confidence: 99%
“…Thus, care should be taken especially when ILAS observed ice PSCs. In this study we eliminated all the ozone data that may have been affected by PSCs occurrence, according to the information on PSCs detection provided by Saitoh et al [2002].…”
Section: Datamentioning
confidence: 99%
“…As temperatures decrease below 195 K, NAT particles and ternary solution droplets [Tabazadeh et al, 1994;Carslaw et al, 1995] form, particle size, area and volume densities, and PSC extinctions increase. Examples of observations of increases in extinction as temperatures decrease are illustrated in CLAES extinction [Massie et al, 1994], Improved Limb Atmospheric Spectrometer (ILAS) [Saitoh et al, 2002], and POAM III [Benson et al, 2006] data. Figures 7a -7d display significant increases in extinction below 195 K. All of the data points correspond to HIRDLS cloud extinction precisions better than 50%.…”
Section: Observations Of Polar Stratospheric Cloudsmentioning
confidence: 99%
“…However, methods of including such processes in largescale models have not yet been developed. However, several other studies have concluded that a significant proportion of observed PSCs cannot be explained by mesoscale ice-formation but by synoptic scale temperature changes (Spang et al, 2001;Saitoh et al, 2002;Fromm et al, 2003;Pagan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tabazadeh et al (2001) have suggested that homogeneous nucleation of NAT may occur at a rate sufficient to denitrify the Arctic stratosphere based on extrapolation of laboratory data by Salcedo et al (2001). However, Knopf et al (2002) have performed new laboratory measurements which indicate that homogeneous nucleation of NAT is too slow to form NAT PSCs, even at temperatures several K below T NAT .…”
Section: Introductionmentioning
confidence: 99%